New and innovative consumer demands and expectations on the Hungarian food market - Töröcsik, Mária; Pál, Eszter; Jakopánecz, Eszter (Acta Agraria Debreceniensis, 2018)
Food and eating have always encompassed more than the simple intake of nutrients; therefore, when thinking about food consumption, we need to examine several groups of influencing factors whose correlations from the aspect of the consumer are described by a complicated matrix. This paper focuses on the selection of signs indicating new and innovative consumer behaviours, and on the megatrends that are the driving forces of transitions and that lead to the consequences of strikingly reconsidered consumer decisions nowadays. The authors stress that there are qualitative and structural changes in food consumption in Hungary, with an increasing quantity of differentiated consumer demands appearing, a few of them influencing our everyday decisions even atthe concept level. The findings of primary research originated from a personal questionnaire survey consisting of 2001 respondents, in which we also focused on the attitude towards eating and media consumption related to gastronomy.This paper is an introduction to the market segments detectable in the present Hungarian population aged 15–74 in the topics concerned.